Globalization, changing demographics, and educational challenges in East Asia - Hannum, Emily; Park, Hyunjoon; Butler, Yuko Goto (Research in sociology of education, 2010)
In recent decades, globalization and regional integration have brought significant economic and demographic changes in East Asia, including rising economic inequality, growing population movements within and across borders, and the emergence or renewed geopolitical significance of cultural and linguistic minority populations. These trends have coincided with significant changes in family formation, dissolution, and structures. How have these changes played out in the diverse educational systems of East Asia? In what innovative ways are East Asian governments addressing the new demographic realities of their student populations? This volume offers a snapshot of key educational stratification issues in East Asian nations, and their evolution in conjunction with changing student populations. Ten empirical pieces address issues ranging from Japan's education reforms and changes in teacher work patterns as the system adapts to globalization; persisting and new forms of educational stratification in China; educational stratification and new multiculturalism in educational policy in Korea; and the ways that migration is shaping education in the city-states of Hong Kong and Singapore. Collectively, the pieces in this volume represent a first attempt to investigate national responses to critical regional trends.